2017
DOI: 10.1590/s1984-29612017041
|View full text |Cite
|
Sign up to set email alerts
|

Hepatozoon caimani in Caiman crocodilus yacare (Crocodylia, Alligatoridae) from North Pantanal, Brazil

Abstract: Hepatozoon species are the most common intracellular hemoparasite found in reptiles. Hepatozoon caimani, whose vectors are Culex mosquitoes, has been detected in a high prevalence among caimans in Brazil by blood smears examinations. The present work aimed to detect and characterize the Hepatozoon spp. found in 33 caimans (24 free-ranging and 9 captive; 28 males and 5 females) (Caiman crocodilus yacare) sampled at Poconé, North Pantanal, state of Mato Grosso, Brazil, using blood smears examinations and molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
1
13
1
Order By: Relevance
“…( B ) Haplotypic network of Hepatozoon sp. generated through mitochondrial gene 18S rRNA sequencing with TCS v.1.21 software 30 . Each line in the network represents a single mutational step; Small circles indicate hypothetical haplotypes that are necessary intermediates among the identified haplotypes, but which were not observed in the sampling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…( B ) Haplotypic network of Hepatozoon sp. generated through mitochondrial gene 18S rRNA sequencing with TCS v.1.21 software 30 . Each line in the network represents a single mutational step; Small circles indicate hypothetical haplotypes that are necessary intermediates among the identified haplotypes, but which were not observed in the sampling.…”
Section: Resultsmentioning
confidence: 99%
“…In samples positive for both of the above PCR protocols, the two Hepatozoon 18S rRNA sequences obtained were concatenated to obtain a large 18S rRNA fragment to be used in phylogenetic analyses (approximately 1400 bp). Hepatozoon caimani DNA obtained from a naturally infected Caiman crocodilus yacare 30 was used as a positive control. Ultra-pure sterile water (Life Technologies ® , Carlsbad, CA, USA) was used as a negative control in all PCR assays.…”
Section: Methodsmentioning
confidence: 99%
“…The DNA positive controls for Leishmania infantum (JUSI et al, 2015), Bartonella henselae (André et al, 2015), Mycoplasma sp. (GONÇALVES et al, 2015), Hepatozoon caimani (BOUER et al, 2017), Babesia vogeli (Jaboticabal strain), Cytauxzoon sp. (ANDRÉ et al, 2009), Ehrlichia canis (Jaboticabal strain), and Anaplasma sp.…”
Section: Fvbp Molecular Screening and Characterizationmentioning
confidence: 99%
“…In addition, blood smear analyses to detect hemoparasites revealed that 26% (6/23) of the animals from site 1 were infected with hemogregarine sensu lato, whereas no hemoparasites were detected in animals from site 2. Conversely, Bouer et al found a higher prevalence of Hepatozoon caimani in captive animals (88.8%; 8/9) than in free‐living animals (70.8%; 20/24) from the northern region of Pantanal (Brazil).…”
Section: Discussionmentioning
confidence: 96%